Enhancing Student Participation in Intensive EFL Classrooms: The Role of Collaborative Learning Strategies - Dian Arsitades Wiranegara; Rendhi Fatrisna Yuniar; Muchamad Adam Basori (English Edu: Journal of English Teaching and Learning, 2026)
Collaborative learning is an effective pedagogical approach that enhances student participation and engagement in language education. This study examines its impact on student motivation, participation, and language proficiency in an English as a Foreign Language (EFL) setting. The research employs a classroom action research design with structured observations, student surveys, and group assessments. Findings indicate that collaborative learning fosters a supportive environment, increasing student confidence in speaking and listening activities. Students demonstrated greater willingness to engage in discussions and improved comprehension skills. The teacher’s role shifts from a knowledge provider to a facilitator, promoting active participation. Despite challenges such as unequal participation and time constraints, structured implementation enhances engagement. These results highlight the importance of collaborative learning in language education, advocating for student-centered models. Future research should explore digital and blended learning tools to further optimize engagement.